DIFFERENTIATED TEACHING CONTENT VIEWED FROM THE STUDENTS’ LEARNING STYLES IN TEACHING WRITING - Elistya, Wenny; Susanti, Yunik; Nurhajati, Diani (Media Inovasi Pendidikan dan Publikasi, 2024)
This research aims to find out the effect of differentiated teaching content viewed from students’ learning style for students’ writing skill in the senior high school. Quantitative approach using experimental research with one-group-pre-test-post-test design was used. The data were collected using questionnaire to know students’ learning style and writing test to know students’ writing ability. The data analyzed using SPSS. The result of data analysis showed that there are visual, auditory, and kinesthetic learning styles and the most common learning style is visual learners. Students' writing skills after being taught using differentiated content improved, it is showed from the results of the pre-test and post-test, pre-test was 59 and post-test was 85,6. The results of the T-Test analysis show that the calculated t-test is higher than the t-table value (42,461 > 2,039) with a significant of 0.000, which means there is significant effect in students' writing abilities after using differentiated teaching content. It can be concluded that teaching methods that adjust learning styles have an effect on students' writing skills, so teacher are suggested to pay attention to students’ learning style when teaching writing.​